SERS detection of prometryn herbicide based on its optimized adsorption on Ag nanoparticles - Rubira, R. J.G. [UNESP]; Furini, L. N.; Constantino, C. J.L. [UNESP]; Sanchez-Cortes, S. (Elsevier, 2021)
The large use of herbicides applied in the control of agricultural pests has become a serious environmental problem. One of the concerns is the long persistence of these contaminants in soil and wastewater leading to the need of developing detection and quantification techniques. In this work, we applied surface-enhanced Raman scattering to detect prometryn herbicide using silver nanoparticles at low concentrations (ppb - parts per billion). The adsorption of prometryn on metallic surfaces was studied at different pH in order to optimize the interaction mechanism with the metal. The effect of pH is especially strong on prometryn, since it undergoes a chemical change at pH < 5 consisting in an hydroxylation of the triazine ring that leads to the hydroxylated prometryn. Thus, the quantitative analysis of prometryn was done at neutral and alkaline pH, at which prometryn interacts with the metal surface through the formation of coordination charge-transfer bonds. The detection of prometryn led to limit of detection of 1.2 × 10−7 mol/L (28 ppb) at pH 11 and 5.3 × 10−7 mol/L (128 ppb) at pH 7. The limit of detection at pH 11 is comparable to the concentration allowed to PRM in potable water by regulating organizations.
Keywords: Herbicide; Prometryn; Quantitative analysis; SERS